Dotação e talento: concepções reveladas em dissertações e teses no Brasil - Anjos, Isa Regina Santos dos (2011)
The research objective was to identify, through the theoretical and methodological approaches, the epistemological profile and trends of research dissertations and theses in the graduate programs in Brazil who studied the care for people with high ability / giftedness. For this study we adapt a paradigmatic scheme proposed by Sánchez Gamboa (2007). Thus, we investigated the following indicators in dissertations analyzed: tier: empirical-analytic, phenomenological-hermeneutic, critical-dialectical; technical level: type of research, technical collection and treatment technique; theoretical level: design education, design service and design of giftedness; epistemological level: design science, design and conception of causality of scientific validation. The predominant research approach in our study corresponded to the hermeneutic-phenomenological approach, which research techniques are used to collect information, in most cases, they referred specifically to interviews, questionnaires, interviews and document analysis. As to theoretical predictions, the analyzed studies are based on theories that purport to criticize, expose and explain the ideologies silenced by a discourse, text or any other type of communication seeking to promote an intersubjective consensus. As for the epistemological level, the research analyzed consider the interpretation of the researcher on the study object as a scientific criterion, since the researcher is able to articulate in a logical and rational reflection on their research.